FORMS OF IDENTIFYING AN ACTIVE PROFESSIONAL POSITION BY SPECIALISTS OF SERVICE SPHERE - Olena A. Ivanova (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The article deals with the problem of identifying an active professional position of specialists in service sphere. It is found that the active professional position of a person is formed on the basis of active life position, the determining factor of which is the level of claims in the conditions in which its potential develops most effectively. The active life position of a person is his ability to perform the functions of selfanalysis, self-control, self-regulation, self-consciousness. Social activity acts as a personal way of relating yourself to other people, determining your position and thus characterizes social responsibility. Social responsibility as a fundamental principle of identifying the active professional position by specialists of service sphere is noted. It is determined that for the formation of the specialists of the service sector, active professional position acquires the importance of the ability to imitate the experience of others, to transform it creatively, to promote and disseminate both the effective results of the improvements of other specialists and their own innovations. The main directions of the active professional position of service specialists are outlined: social orientation, creativity, social communication, self-improvement. The features of communication activity in the professional position of a specialist in services include: social orientation, accessibility (participation in volunteer activities, grant programs), the ability to “sell themselves in the labor market”, the implementation of professional lifts. The understanding of the word “sell” in the indirect sense as the ability to talk about raising wages, salary; presentation of the value of their own time and professional resources to the employer; the ability to agree on improving the conditions of work comfort. It is noted that the ability to organize and maintain professional communication reveals a constructive professional position of a specialist – one that is formed on the basis of awareness of certain values (activity, effectiveness, respect for others, indifference, pragmatism, and the like). The value attitude to professional communication is a component of the value-semantic sphere of personality that positively reflects the system of values of communicative knowledge and defines purposeful activity of students on their mastering and understanding the need of knowledge of oneself as a communicative personality. The forms of active professional position manifestation by the service sector specialists are highlighted: professional trainings, professional development, acquisition of additional competencies that are aimed at self-improvement, creativity, social communication, provided that the professionally active specialist takes into account the social situation in society, has a positive attitude to professional retraining according to the needs of industry development.